Arah dan Perkembangan Politik Hukum di Indonesia - M Zen Abdullah (Jurnal LEX SPECIALIS, 2011)
In order to maintain the status quo power that lasting, often apply the legal system of the orthodox / conservative, which is more reflective of a legal product that generated more social vision of delivering the impression of government than the interests of the community expected peoples. The legal system that is built more responsive / populists are more concerned with the social interests of the will of the people.Given the conservative legal system by producing a legal product that is less responsive / populist thus reflects less a sense of justice because it is not based on state laws that live and thrive in the midst of society. For that, there is need for donations directed to place the political thinking of law in a central position very respectable, well-reviewed culturally, intellectually and in the implementation of the concrete. By replacing the position of the flow of legal positivism caracter intrumentalis conservative through alignment and harmonization of its values with the situation and legal conditions that developed in the midst of society by observing the flow sosiolocigal prakmatic yurisprudence and realism that characterized the law responsive / populist, it is necessary to reform efforts konkritisasi law through the development theory proposed by Prof. Muchtar Kusumaatmadja, by taking various steps that need immediate reform, improve and perfect guidance through national law by holding reforms, codification and unification in certain areas of law, order the functions of legal institutions according to their respective portions and increase the ability and authority law enforcement officials.Key Note : Directions and Developments in Political Law